Picomolar Dopamine Detection using Colloidal Surface-Enhanced Raman Scattering Based on Benzene-Dithiol–Linked Gold Nanoparticles in Solution - Sucharitakul, Waraporn; Danvirutai, Pobporn; Pinlaor, Somchai; Piyawattanametha, Wibool; Srichan, Chavis (My University, 2026)
Sensitive detection of dopamine at ultralow concentrations is essential for the development of advanced chemical and neurochemical sensing technologies. Surface-enhanced Raman scattering (SERS) offers molecular specificity and high sensitivity, but its analytical reliability is often limited by poor signal reproducibility arising from uncontrolled nanoparticle aggregation. In this work, we report a solvent-based colloidal SERS platform for picomolar dopamine detection using benzene-1,4-dithiol (BDT)–linked gold nanoparticles (AuNPs). BDT serves as a molecular linker that defines sub-nanometer plasmonic nanogaps and simultaneously acts as an intrinsic Raman reference. Dopamine molecules introduced in dilute solution are efficiently sampled within these nanogaps through noncovalent interactions, resulting in strong and reproducible SERS enhancement. The proposed platform demonstrates a detection limit in the picomolar range, a wide linear dynamic response, and excellent signal stability without the use of biological or artificial matrices. This study presents a solvent-based SERS strategy for quantitative liquid-phase dopamine detection in aqueous environments, offering a foundation for further development in sensor calibration and integration with biological matrices.
Keywords: Benzene dithiol; Dopamine sensing; Gold nanoparticles; Picomolar detection; Surface-enhanced raman scattering